ADOPTING A STRICT LIABILITY APPROACH TOWARD GENOCIDE (UCC Law Journal, 2024)
The Genocide Convention lists intent as a critical element that must be proven to secure convictions for genocide. Many defendants have been acquitted or convicted of lesser crimes due to the difficulty in proving genocidal intent. The argument presented in this paper is that the large-scale negative impact of genocide on humanity should be considered when defining its scope in penal legislation. A fortiori, the crime of genocide should be given similar consideration to other crimes that have been classified as strict liability crimes due to their severity and cost to society. Intent as an element should, therefore, be deduced from the general purpose of the perpetrator’s acts. Although the strict legality principle is not perfect and has some flaws, it is still the most just, effective, coherent, persuasive, and proper reading of the genocide convention. The goal here is to contribute to the conversation on the limitations of genocidal intent to the effectiveness of the enforcement of the crime of genocide in international criminal law.